The value of extracorporeal photopheresis as an immunosuppression-modifying approach in solid organ transplantation: a potential solution to an unmet medical need - Augusto, Jean-François; Benden, Christian; Diekmann, Fritz; Zuckermann, Andreas (Frontiers in Immunology, 2024)
Allograft rejection is a critical issue following solid organ transplantation (SOT). Immunosuppressive therapies are crucial in reducing risk of rejection yet are accompanied by several significant side effects, including infection, malignancy, cardiovascular diseases, and nephrotoxicity. There is a current unmet medical need with a lack of effective minimization strategies for these side effects. Extracorporeal photopheresis (ECP) has shown potential as an immunosuppression (IS)-modifying technique in several SOT types, with improvements seen in acute and recurrent rejection, allograft survival, and associated side effects, and could fulfil this unmet need. Through a review of the available literature detailing key areas in which ECP may benefit patients, this review highlights the IS-modifying potential of ECP in the four most common SOT procedures (heart, lung, kidney, and liver transplantation) and highlights existing gaps in data. Current evidence supports the use of ECP for IS modification following SOT, however there is a need for further high-quality research, in particular randomized control trials, in this area.